PERCEPTIONS OF HIGHER EDUCATION INSTITUTIONS IMPACT ON DIFFERENT DIMENSIONS OF QUALITY OF LIFE AND RESIDENTS' OVERALL LIFE SATISFACTION - Marta Alves; Helena Alves; Eugénia Pedro; João Capucho (International Journal for Quality Research)
An innovative theoretical model analyses the association between community residents' perceptions of higher education institutions (HEI) impact on different dimensions of quality of life (economic, social, environmental, health and safety) and residents' overall life satisfaction. A total of 550 individuals who lived in a region of Portugal with an HEI participated in the study. The responses were analysed through a Partial Least Squares - Structural Equation Model (PLS-SEM). Results revealed that both economic and social dimensions of the perceived impact of HEI have a positive effect on citizens' own level of life satisfaction, and that environmental dimension shows a negative effect. No effects were observed concerning safety and health perceived impact. Therefore, several public policies must be implemented to sustain citizens' positive perception of economic and social dimension, transform the negative perception of the environmental impact of HEI, and promote a positive perception in terms of health and safety impact.